Best perioperative practice in management of ambulatory patients with obstructive sleep apnea. Issue 6 (December 2018) - Nagappa, Mahesh; Subramani, Yamini; Chung, Frances
Abstract : Purpose of review: The perioperative outcome in obstructive sleep apnea (OSA) patients undergoing ambulatory surgery can be potentially impacted by the type of anesthetic technique, fluid management and choice of anesthetic agents. This review highlights the best perioperative practices in the management of OSA patients undergoing ambulatory surgical procedures. Recent findings: A recent meta-analysis found that STOP-Bang might be used as a perioperative risk stratification tool. Patients with high-risk OSA (STOP-Bang ≥3) were found to be associated with an increased risk of postoperative complications and prolonged length of hospital stay compared with low-risk OSA (STOP-Bang 0-2) patients undergoing noncardiac surgical procedures. A bidirectional relationship exists between OSA and difficult airway. Both suspected or diagnosed OSA may be associated with either difficult intubation or difficult mask ventilation or both. A recent meta-analysis identified OSA as an important risk factor for opioid-induced respiratory depression. A dose–response relationship was shown between the morphine equivalent daily dose and death or near-death events in OSA patients undergoing surgery. Postoperative continuous monitoring is recommended for high-risk OSA patients receiving opioids. Minimising the dose of muscle relaxant, neuromuscular monitoring and ensuring complete reversal of neuromuscular blockade before extubation is essential in OSA patients to avoid postoperative complications. Whenever feasible, regional anesthesia with multimodal analgesia may be considered as a better alternative to general anesthesia in OSA patients. Summary: Patients with OSA and associated comorbidities present a challenge to anesthesiologists as they are at a high risk of perioperative complications. It is important to identify patients with OSA, with the goal to raise awareness among providers, mitigate risk and improve outcomes.